Future Global Visions of Engineering Education - Wisuit Sunthonkanokpong (My University, 2011)
This article presents the future global visions of engineering education. Due to the socio-technological challenges, engineering education must anticipate and adapt to dramatic changes in terms of engineering practice and instruction. In the future, the roles of engineers must change along with the following aspects: the globalization of industry and engineering practice, the shift of engineering employment from large companies to small and medium-sized companies, the growing emphasis on entrepreneurialism, the growing share of engineering employment in nontraditional, less-technical engineering work, the shift to a knowledge-based “services” economy, and increasing opportunity for using technology in the education and work of the engineering. This study found that successful attributes for the engineering education graduates in 2020 must be at strong level. They are as follows: lifelong learners, ability to frame problems, putting them in a socio-technical and operational context, dynamic/agile/resilient/flexible, high ethical standards and a strong sense of professionalism, good communication skills with multiple stakeholders, possess strong analytical skills, exhibit practical ingenuity; posses creativity, and business and management skills; leadership abilities. Moreover, the study found that the problems which engineering education graduates in 2020 encounter and have strong ability to solve. They are as follows: maintaining technical currency & life long learning, environmental and energy related problems, managing globalization, problems related to population growth, ultra-nanoscale, miniaturization, and bioengineering and medical problems.
Keywords: Ingenuity; Vision; Health systems engineering; Engineering Education and Technology